Pembentukan Norma Ekonomi Islam Dalam Lintasan Sejarah: Dari Pasar Madinah Hingga Sistem Hisbah - Ridwan Maulana Akbar; Dewi Nur Anisa Rahmawati; Ahmad Fajar Siddiq (Jurnal Adab dan Peradaban Islam, 2026)
This study examines the historical formation of Islamic economic norms, tracing the evolution from the Madinah market model established by the Prophet Muhammad to the sophisticated hisbah (market supervision) system developed across classical Islamic civilizations. The research aims to analyze how Islamic economic ethics, market regulations, and supervisory institutions emerged, developed, and functioned as an integrated normative framework for Islamic economic governance. Employing a qualitative historical-institutional approach with library research design and comparative normative analysis, this study draws upon classical Islamic jurisprudence, hadith literature, and contemporary Indonesian economic scholarship. The findings reveal three interconnected dimensions: first, the Madinah market as a foundational model of ethical market governance; second, the evolution of hisbah as an institutionalized mechanism of market integrity and social justice; third, the normative principles underlying Islamic economic ethics that transcend historical periods. This study concludes that the classical Islamic normative framework for economic governance offers a sophisticated and deeply relevant model for addressing contemporary challenges of market ethics, consumer protection, and equitable economic development in Indonesia.